Distribution of dfrA1 and cat1 antibiotic resistance genes in uropathogenic Escherichia coli isolated from teens pregnant women in Iraq - Mohammed, Rana Kadhim; Ibrahim, Ali Attaallah (Iraqi Journal of Science, 2022)
The present study aims to detect the distribution of dfrA1 and cat1 antibiotic resistance genes among uropathogenic Escherichia coli (UPEC) in pregnant teen women and determine their susceptibility to common antibiotic uses. We collected urine (116) samples from patients in hospitals in Baghdad, Iraq. Isolation and identification of bacteria (culturing, biochemical test, and genetically by 16S rRNA gene), antibiotic susceptibility tests (eight antibiotics), and detection of the dfrA1 and cat1 resistance genes, and used SPSS program for statistically analyzing the results. The distributed UPEC in patients most than another causative agent in percentage (50%). It was highly resistant to Trimethoprim (82%) and Cefotaxime (82%) antibiotics. And they highly distributed frequency for dfrA1-gene (Trimethoprim resistance gene) (74%) than cat1-gene (Chloramphenicol resistance gene) (38%).